Stress Heterogeneity and the Onset of Faulting Along Geometrically Irregular Faults. Issue 17 (9th September 2022) - Morad, Doron; Lyakhovsky, Vladimir; Hatzor, Yossef H.; Sagy, Amir
Abstract: We present a two‐dimensional analytical solution for the static stress field around a rough interlocked interface under background stresses and its applications to faulting. The solution is derived using perturbation theory for the defined interface topography and background stresses. The failure‐ratio, which scales the likelihood to failure of the bulk material around the interface, is calculated adopting the Coulomb failure criterion. We compare model predictions with results of experiments performed on rough rock interfaces and find good agreement between the locations of off‐fault deformation zones and calculated high failure‐ratio values. We further study the effect of fault topography on stress distribution and failure around the San Andreas Fault and find a moderate correlation between Failure‐Ratio values and off‐fault seismic events. We conclude that our model is able to delineate off‐fault regions that are relatively prone to bulk failure due to local effects of fault topography. Plain Language Summary: An earthquake is triggered when the stress build‐up by tectonic motion exceeds the strength of the fault material. The factors that control the earthquake magnitude, location, and time are still largely unknown. The significance of fault roughness to earthquake physics has been recognized for many years; geometrical irregularities across fault zones drive stress heterogeneities that strongly affect the onset of seismic rapture. Different research groups are now attempting to quantify the effect of roughness on faulting, either experientially or theoretically. Particularly, it has long been attempted to develop an analytical solution for the local stress field and yield potential across interlocked interfaces as a proxy to natural faulting, albeit without much success. Here, we present an analytical model that solves the stress field around an interlocked fault segment for a given interface roughness and background stress field, and show how surface geometry affects rock failure around the interface. We argue that any dynamic sliding between surfaces is initiated by fracture of the intact rock material at immediate proximity to the interface. We use the stresses obtained by our analytical solution to assess the failure potential around seismically active faults, a novel contribution with specific implications to seismic risk assessment. Key Points: Analytical solution demonstrates how surface geometry and background stress affect the local stress field around rough interlocked faults The stress undulations induced by the rough interface and the background stress field, decay exponentially away from the fault The likelihood for off‐fault failure is assessed using the Coulomb failure criterion and is demonstrated on laboratory and natural faults